Konflik Interpersonal Pasca Konversi Agama di Kalangan Muallaf - Arafat Noor (LPPM Institut Agama Islam Al-Hikmah Tuban, 2020)
Abstract, this work is based on the results of field research which is motivated by interpersonal conflicts of converts. Interpersonal conflict between converts with family and friends caused by disagreement with the decision to convert to Islam. Researcher's interest lies in the process of resolving interpersonal conflicts withfamily and friends. The way for converts to resolve conflicts is through negotiation and mediation with the help of those closest to us and from the Yogyakarta Center for Mualaf advocacy team. This study uses a social psychology approach and Lewis R. Rambo's conversion theory model, Simon Fisher's conflict stage analysis, and conflict resolution. Researchers used the life history method to reveal the experience of religious converts and hidden information based on the life history of converts relating to post-conversion conflicts. Data collection includes participatory observation, interviews, questionnaires, and documentation. Data analysis was performed using data reduction procedures, data presentation and data verification using the triangulation method, and drawing conclusions. The results showed: 1) Sources of interpersonal conflict between converts with family and relatives from the previous religious environment in the form of conflict based on differences in personality, differences in cultural and religious values, different interests or needs in religion. The existence of negative prejudice and stereotypes accompanied by feelings of disappointment and frustration can resulting in discrimination and acts of violence. 2) How to resolve interpersonal conflicts of converts relate to the consequences of post-conversion. Converts try to understand the conversion made to parents and relatives from previous religious environments in order to avoid misperceptions. The consequences after the conversion are similar to the religious stability of the converts which is shown by using the principles in Islamic teology, namely tabayun through negotiation and mediation processes. Keyword: Interpersonal Conflict, Religious Conversion, Mualaf